Neural biomarkers of risk for psychosis - Demro, Caroline (My University, 2015)
Schizophrenia is a potentially debilitating mental disorder which is usually preceded by one to two years of attenuated psychotic symptoms. The identification of individuals at psychosis-risk has relied on self-report and interview measures, which have limited specificity. Early identification could benefit from the discovery of biomarkers that may add accuracy of identification when used in conjunction with the self-report measures. Proton Magnetic Resonance Spectroscopy is an imaging technique used to quantify brain metabolites. Development of psychosis may be associated with metabolite concentration changes that reflect an alteration in glutamatergic mechanisms. Elevated glutamate levels have been observed in the striatum of individuals at psychosis-risk and individuals in their first episode of schizophrenia as compared to healthy controls. The current study explored glutamatergic metabolite concentrations in the striatal and cingulate gyri as potential biomarkers to aid in the understanding of psychosis-risk symptoms.
Keywords: biomarker; glutamate; glutathione; psychosis; risk; spectroscopy